Pneumococcal carriage in vaccine-eligible children and unvaccinated infants in Lao PDR two years following the introduction of the 13-valent pneumococcal conjugate vaccine - Satzke, Catherine; Dunne, Eileen M.; Choummanivong, Molina; Ortika, Belinda D.; Neal, Eleanor F.G.; Pell, Casey L.; Nation, Monica L.; Fox, Kimberley K.; Nguyen, Cattram D.; Gould, Katherine A.; Hinds, Jason; Chanthongthip, Anisone; et al. (Vaccine, 2019)
Pneumococcal carriage is a prerequisite for disease, and underpins herd protection provided by pneumococcal conjugate vaccines (PCVs). There are few data on the impact of PCVs in lower income settings, particularly in Asia. In 2013, the Lao People's Democratic Republic (Lao PDR) introduced 13-valent PCV (PCV13) as a 3 + 0 schedule (doses at 6, 10 and 14 weeks of age) with limited catch-up vaccination. We conducted two cross-sectional carriage surveys (pre- and two years post-PCV) to assess the impact of PCV13 on nasopharyngeal pneumococcal carriage in 5–8 week old infants (n = 1000) and 12–23 month old children (n = 1010). Pneumococci were detected by quantitative real-time PCR, and molecular serotyping was performed using DNA microarray. Post PCV13, there was a 23% relative reduction in PCV13-type carriage in children aged 12–23 months (adjusted prevalence ratio [aPR] 0.77 [0.61–0.96]), and no significant change in non-PCV13 serotype carriage (aPR 1.11 [0.89–1.38]). In infants too young to be vaccinated, there was no significant change in carriage of PCV13 serotypes (aPR 0.74 [0.43–1.27]) or non-PCV13 serotypes (aPR 1.29 [0.85–1.96]), although trends were suggestive of indirect effects. Over 70% of pneumococcal-positive samples contained at least one antimicrobial resistance gene, which were more common in PCV13 serotypes (p < 0.001). In 12–23 month old children, pneumococcal density of both PCV13 serotypes and non-PCV13 serotypes was higher in PCV13-vaccinated compared with undervaccinated children (p = 0.004 and p < 0.001, respectively). This study provides evidence of PCV13 impact on carriage in a population without prior PCV7 utilisation, and provides important data from a lower-middle income setting in Asia. The reductions in PCV13 serotype carriage in vaccine-eligible children are likely to result in reductions in pneumococcal transmission and disease in Lao PDR.